Essays on international migration - Chowdhury, Mehdi Mahmud (2011)
In recent time efforts are observed in re-evaluating the linkage between economic development and international migration. The thesis can be considered as an attempt to add something to those efforts. In this thesis we mainly analyse the effects of competition among the countries in international labour market and effects of migration on the research activities of firms. As appeared, these two issues so far have not received much attention of economic literature.